1996
DOI: 10.1007/bf00051124
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent or continuous transdermal nitroglycerin: Still an issue, or Is the case closed?

Abstract: After a decade of controversy and debate, many experts have now concluded that continuous nitroglycerin patch treatment leads to complete tolerance development and therefore cannot be recommended for any angina patient. This conclusion is largely based on the disappointing results of the large Transdermal Nitroglycerin Cooperative Study, in which continuous patch treatment in doses of 15-105 mg daily failed to increase exercise duration more than placebo after 2 and 8 weeks of treatment. However, other well-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…For instance, problems in correct identification of drug packages are likely to be associated with decreased adherence , as are difficulties in handling drugs during the personalization process (e.g. tablet splitting ), whereas errors in drug dosage and drug application are related to non‐response or toxicity . Hence, the prevention of drug administration errors appears important, particularly in the ambulatory care setting, where the incidence rate might be higher and subsequent strategies to counteract adverse outcomes following administration errors might be less accessible.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, problems in correct identification of drug packages are likely to be associated with decreased adherence , as are difficulties in handling drugs during the personalization process (e.g. tablet splitting ), whereas errors in drug dosage and drug application are related to non‐response or toxicity . Hence, the prevention of drug administration errors appears important, particularly in the ambulatory care setting, where the incidence rate might be higher and subsequent strategies to counteract adverse outcomes following administration errors might be less accessible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the problems of variable drug absorption and fluctuating plasma concentrations caused by GTN ointment were overcome by the transdermal patch or tape system. The continuous use of transdermal GTN tape can still lead to nitrate tolerance [2]. Recent data suggest that the intermittent application of transdermal GTN may be associated with decreased exercise capacity as well as the development of unstable angina when the tape is not applied [3].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study, conducted in rats, was to confirm whether nitrate tolerance observed after chronic administration of organic nitrates to rats is due to the reduced P-450 catalyzed biotransformation of these organic nitrates to NO. In addition to the current strategy of intermittent therapy with an adequate nitrate-free interval, 6,7 P450 induction may become an effective strategy to prevent nitrate tolerance.…”
Section: Introductionmentioning
confidence: 99%